The impact of oil price volatility on macroeconomic activity in Russia - Katsuya Ito (Colegio de Economistas de A Coru\~na, 2010)
Since the beginning of the 1980s a large number of studies using a vector autoregressive (VAR) model have been made on the macroeconomic effects of oil price changes. However, surprisingly few studies have so far focused on Russia, the world's second largest oil exporter. The purpose of this paper is to empirically examine the impact of oil prices on the macroeconomic variables in Russia using the VAR model. The time span covered by the series is from 1994:Q1 to 2009:Q3, giving 63 observations. The analysis leads to the finding that a 1% increase (decrease) in oil prices contributes to the depreciation (appreciation) of the exchange rate by 0.17% in the long run, whereas it leads to a 0.46% GDP growth (decline). Likewise, we find that in the short run (8 quarters) rising oil prices cause not only the GDP growth and the exchange rate depreciation, but also a marginal increase in inflation rate.
Keywords: Q4; 330; co-integration test; impulse response functions; oil prices; Russia